At the intersection between toxicology and physiology: What we have learned about sea lampreys and bony fish physiology from studying the mode of action of lampricides - Birceanu, Oana; Tessier, Laura R.; Huerta, Belinda; Li, Weiming; McDonald, Allison; Wilkie, Michael P. (Journal of Great Lakes Research, 2021)
The lampricides 3-trifluoromethyl-4-nitrophemol (TFM) and niclosamide have been used for over 60 years to control the invasive sea lamprey (Petromyzon marinus) population in the Laurentian Great Lakes. In this review, we summarize these findings in the context of the mode of action of both lampricides, with a focus on: (1) the physiology of uptake, bodily distribution and mode of action, detoxification, and excretion of lampricides in lamprey and non-target fishes, (2) the development of an Adverse Outcome Pathway for TFM and niclosamide, and (3) the identification of novel avenues for future research that can be further explored to ensure continuous suppression of the sea lamprey population in the Great Lakes. We explored how research on the mode of action of lampricides has provided novel insights into the gill microenvironment and how this impacts lampricide toxicity; described new information on mitochondria and tissue physiology; and discussed how the activity of enzymes that are involved in detoxification pathways impacts the response of fishes to xenobiotics. Considering the information that has been generated over the years on sea lamprey and bony fish physiology from studying the mode of action of lampricides, here we propose an Adverse Outcome Pathway for TFM and niclosamide and identify novel avenues for research on the short and long-term effects of lampricide applications, either alone or in combination. Lastly, we discuss how the differences in physiology between sea lampreys and non-target fishes can be further exploited to ensure continuous suppression of the sea lamprey population in the Great Lakes.
Keywords: Invasive species; Lampricides; Niclosamide; Physiology; TFM; dept.che; peer-reviewed

Diel Patterns of Pheromone Release by Male Sea Lamprey - Fissette, Skye D; Bussy, Ugo; Huerta, Belinda; Brant, Cory O; Li, Ke; Johnson, Nicholas S; Li, Weiming (Integrative and Comparative Biology, 2021)
Costs to producing sexual signals can create selective pressures on males to invest signaling effort in particular contexts. When the benefits of signaling vary consistently across time, males can optimize signal investment to specific temporal contexts using biological rhythms. Sea lamprey, Petromyzon marinus, have a semelparous life history, are primarily nocturnal, and rely on pheromone communication for reproduction; however, whether male investment in pheromone transport and release matches increases in spawning activity remains unknown. By measuring (1) 3keto-petromyzonol sulfate (3kPZS, a main pheromone component) and its biosynthetic precursor PZS in holding water and tissue samples at six points over the course of 24 hours and (2) 3kPZS release over the course of several days, we demonstrate that 3kPZS release exhibits a consistent diel pattern across several days with elevated pheromone release just prior to sunset and at night. Trends in hepatic concentrations and circulatory transport of PZS and 3kPZS were relatively consistent with patterns of 3kPZS release and suggest the possibility of direct upregulation in pheromone transport and release rather than observed release patterns being solely a byproduct of increased behavioral activity. Our results suggest males evolved a signaling strategy that synchronizes elevated pheromone release with nocturnal increases in sea lamprey behavior. This may be imperative to ensure that male signaling effort is not wasted in a species having a single, reproductive event.
Keywords: dept.che; peer-reviewed

Early life interactions with aquatic insects elicit physiological and behavioral stress responses in lake sturgeon (Acipenser fulvescens) - Wassink, Lydia; Riedy, Joseph J.; Huerta, Belinda; Johnson, Garrett; Larson, Douglas L.; Li, Weiming; Scribner, Kim T. (Environmental Biology of Fishes, 2021)
Predator encounters during early life can elicit behavioral and physiological responses that have fitness consequences during subsequent prey life stages. In threatened lake sturgeon (Acipenser fulvescens) and other lithophilic-spawning fishes, newly hatched larvae (free embryos) are exposed to abundant predators including aquatic insect larvae that co-occupy stream substrates. We investigated stress effects on lake sturgeon larvae after encounters with common aquatic insect predators by quantifying mortality, body size, cortisol levels, and swimming behavior. Free embryos were exposed to either Perlidae (stonefly obligate predators) or Isonychiidae (mayfly filterers and facultative predators) or to no predators (controls). Free embryos that encountered perlids experienced high mortality, elevated cortisol levels, and exhibited cortisol reactivity when subsequently exposed to an acute stressor. Free embryos that encountered isonychiids exhibited elevated mortality, and elevated cortisol and cortisol reactivity relative to controls. Findings indicate that lake sturgeon free embryos are stressed by exposure to members of benthic stream communities during early life stages (predation of nearby conspecifics), and that metrics of stress exhibited threat sensitivity. Data are consistent with predictions that individuals modulate antipredator behavior in response to the intensity of perceived predation threat in the environment. We determined that behavioral outcomes associated with encounters with aquatic insects altered future behavioral trajectories, potentially as an adaptive response that can affect predation rates in subsequent life stages. Results contribute to a broader understanding of how interspecies interactions among co-occurring predator and prey communities may impact individual fitness and fish population recruitment.
Keywords: Aquatic invertebrates; Behavioral plasticity; Early life mortality; Lake sturgeon; Threat sensitivity; dept.che; peer-reviewed

Monitoring of emerging contaminants of concern in the aquatic environment: a review of studies showing the application of effect-based measures - Yusuf, Azeez; O'Flynn, Dylan; White, Blanaid; Holland, Linda; Parle-McDermott, Anne; Lawler, Jenny; McCloughlin, Thomas; Harold, Denise; Huerta, Belinda; Regan, Fiona (Analytical Methods, 2021)
Water scarcity is increasingly a global cause of concern mainly due to widespread changes in climate conditions and increased consumptive water use driven by the exponential increase in population growth. In addition, increased pollution of fresh water sources due to rising production and consumption of pharmaceuticals and organic chemicals will further exacerbate this concern. Although surface water contamination by individual chemicals is often at very low concentration, pharmaceuticals for instance are designed to be efficacious at low concentrations, creating genuine concern for their presence in freshwater sources. Furthermore, the additive impact of multiple compounds may result in toxic or other biological effects that otherwise will not be induced by individual chemicals. Globally, different legislative frameworks have led to pre-emptive efforts which aim to ensure good water ecological status. Reports detailing the use and types of effect-based measures covering specific bioassay batteries that can identify specific mode of actions of chemical pollutants in the aquatic ecosystem to evaluate the real threat of pollutants to aquatic lives and ultimately human lives have recently emerged from monitoring networks such as the NORMAN network. In this review, we critically evaluate some studies within the last decade that have implemented effect-based monitoring of pharmaceuticals and organic chemicals in aquatic fauna, evaluating the occurrence of different chemical pollutants and the impact of these pollutants on aquatic fauna with special focus on pollutants that are contaminants of emerging concern (CEC) in urban wastewater. A critical discussion on studies that have used effect-based measures to assess biological impact of pharmaceutical/organic compound in the aquatic ecosystem and the endpoints measurements employed is presented. The application of effect-based monitoring of chemicals other than assessment of water quality status is also discussed.
Keywords: dept.che; peer-reviewed